Evaluation of the performance characteristics of the European Lightning Detection Network EUCLID in the Alps region for upward negative flashes using direct measurements at the instrumented Säntis Tower. Issue 2 (19th January 2016) - Azadifar, Mohammad; Rachidi, Farhad; Rubinstein, Marcos; Paolone, Mario; Diendorfer, Gerhard; Pichler, Hannes; Schulz, Wolfgang; Pavanello, Davide; Romero, Carlos
Abstract: In this paper, we present a performance analysis of the European Cooperation for Lightning Detection (EUCLID) lightning detection network using data obtained on lightning currents measured at the Säntis Tower (located in northeastern of Switzerland) from June 2010 to December 2013. In the considered period of analysis, a total number of 269 upward negative flashes were recorded at the Säntis Tower. The performance of the EUCLID lightning detection network is evaluated in terms of detection efficiency, location accuracy, and peak current estimates for upward flashes. Excluding flashes containing only an initial continuous current with no superimposed pulses exceeding 2 kA, the flash detection efficiency for upward flashes is estimated to be 97%. The recorded flashes contained a total of 2795 pulses (including return strokes and International Conference on Communications pulses characterized by risetimes lower than 8 µs and peaks greater than 2 kA). The overall pulse detection efficiency was found to be 73%. For pulses with peak values higher than 5 kA, the pulse detection efficiency was found to be about 83%. Peak current estimates provided by the EUCLID network were found to be significantly larger than their directly measured counterparts. This overestimation might be attributed to the enhancement of the radiated electromagnetic fields associated with the presence of the tower and the mountain. The median of the absolute distance error, defined as the median distance between the Säntis Tower location and the EUCLID's stroke locations, was found to be 186 m, the majority of large location errors being associated with measured current peaks lower than 10 kA. The analysis revealed also that the location accuracy of the EUCLID network improved significantly in 2013 as a result of an upgrade in the location algorithms to take into account propagation effects. Key Points: The overall pulse detection efficiency for upward flashes was found to be 73% The detection efficiency for upward flashes with pulses larger than 2 kA was estimated to be 97% The median of the absolute distance location error for upward flashes was found to be 186 m